Recognition and Foreign Domestic Helpers in Hong Kong: The Non-governmental Organizations (NGOs) as a Support System - Xu, Lingzi (International Journal of Social Sciences and Public Administration, 2024)
This paper investigates the effectiveness of non-governmental organizations (NGOs) in supporting foreign domestic helpers (FDHs) in Hong Kong, focusing on the often-overlooked perspectives of the FDHs themselves. Through in-depth interviews with 5 FDHs and consultations with key NGOs, this paper employs recognition theory to analyze the challenges FDHs face due to their marginalized status and to evaluate the impact of NGO support on their recognition and rights within Hong Kong society. The findings reveal both the limitations and strengths of NGOs in advocating for FDHs, providing detailed insights into how these organizations can strengthen their support roles.